875. Sex Differences in Academic Achievement and Faculty Rank in Academic Infectious Diseases. (26th November 2018) - Manne-Goehler, Jennifer; Kapoor, Neena; Blumenthal, Daniel; Stead, Wendy
Abstract: Background: Sex differences in faculty achievement in academic medicine have been described, but little is known about these differences in infectious diseases (ID). This study assesses differences in faculty rank between female and male infectious disease faculty with academic appointments at US medical schools. Methods: We analyzed a complete database of US physicians with medical school faculty appointments in 2014. This database consists of a linkage between the American Association of Medical Colleges faculty roster and a comprehensive physician database from Doximity, a professional networking website for doctors and includes physician age, sex, years since residency completion, publications, National Institutes of Health grants, and registered clinical trials for all academic physicians by specialty. We estimated sex differences in key metrics of academic achievement, including publications and faculty rank, among faculty physicians within ID. Multivariable regression models with medical school-specific fixed effects were used to assess sex differences in full professorship by specialty and the relationship between these factors and achieving the rank of full professor within ID. Results: Among 2, 016 academic ID physicians [Female: 742 (37%)], women accounted for 48.1% of assistant professors, 39.7% of associate professors, and 19.2% of full professors, when compared with men at each level. Women faculty members were younger than men (mean: 48.4 years vs. 54.0 years, P < 0.001) and had fewer total (mean: 24.1 vs. 37.8, P < 0.001) and first/last author publications (mean: 16.7 vs. 32.2, P < 0.001). In adjusted models, the rate of full professorship (vs. assistant or associate) among female compared with male infectious disease physicians was large and highly significant (absolute adjusted difference = −8.0%; 95% confidence interval [CI]: −11.9% to −4.1%). This adjusted difference was greater in ID than in cardiology (−4.7%, 95% CI: −7.9% to −1.3%), hematology (−1.5%, 95% CI: −6.2% to 3.2%), or endocrinology (−0.2%, 95% CI: −4.9% to 4.6%). Conclusion: Significant sex differences in publications and achieving the rank of full professor exist in academic ID, after adjustment for multiple factors known to influence these outcomes. Greater efforts should be made to address equity in academic ID. Disclosures: All authors: No reported disclosures.